في بعض المعايير الفسلجية والمناعية والتغييراتEntamoeba histolytica Nigella sativa تأثير المستخلص المائي لبذور الحبة السوداء النسجية لذكور الفئران المختبرية المصابة بطفيلي: Effect of aqueous extract of Black Seed ( Nigella sativa ) in some Physiological and Immunological parameters and Histological Changes of male mice infected with Entamoeba histolytica - حسين, علي مانع (University of Thi-Qar Journal of Science, 2013)
This study was designed to investigated effect of aqueous extract of Black seeds (Nigella sativa) in somemphysiological and immunological parameters and histological changes of male mice infected with Entamoeba histolotica which divided into four groups, the first group administrated 0.1 ml normal saline orally (control group) , the second group administrated 0.5 ml suspension of Entamoeba histolotica orally ,the third group administrated 1 ml suspension of Entamoeba histolotica orally and the fourth group administrated 1 ml suspension of Entamoeba histolotica and treated after infection with 1 mg extract of black seeds for 10 days.The results showed non significant decreased in concentration of Hemoglobin in second and third group compare with control group and a significant increased in the total count of W.B.C., Lymphocyte, Acidophile and Phagocytosis in second and third group compare with control group (p≤0.05). Results of the current study revealeda significant decreased in P.C.V. and Monocyte, in second and third group and body weight in third group and neutrophil in second group compare with control group and non significant differences in count of Basophile between all groups (p≤0.05) . The results showed also non significant differences in blood parameters, Phagocytosis and body weight in fourth group compare with control group (p≤0.05).